2019
DOI: 10.1016/j.wombi.2018.08.160
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic role of video diaries: A qualitative study involving breastfeeding mothers

Abstract: Background: Despite breastfeeding providing maximum health benefits to mother and baby, many women in the United Kingdom do not breastfeed, or do so briefly.Purpose: Using tenets of ethnography, this study aimed to explore the everyday experiences of first time breastfeeding mothers in the early weeks following birth.Methods: Using a camcorder, five mothers in the United Kingdom captured their real-time experiences in a video diary, until they perceived their infant feeding was established. Using a multidimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…All participating breastfeeding mothers were British Europeans aged between 20 and 29 years and cohabiting or married. Using the Standard Occupational classification [39] before the birth, the women were classified in groups 2-10 with group 10 added for unemployed/student [25].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All participating breastfeeding mothers were British Europeans aged between 20 and 29 years and cohabiting or married. Using the Standard Occupational classification [39] before the birth, the women were classified in groups 2-10 with group 10 added for unemployed/student [25].…”
Section: Resultsmentioning
confidence: 99%
“…A pilot study involved one breastfeeding mother and baby, which included assessing whether the sampling and recruitment strategy were useful, and the camcorder along with some simple guidance was an effective research tool [24]. The pilot resulted in more than 11 h of rich data which were therefore included in the main study [25]. Published studies involving video diaries recruiting between three [26] and 20 participants [27] have been shown to produce abundant data and the pilot study confirmed both the breadth and depth of data that could be collected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Journal-based qualitative methods in sociology were initially developed in order to facilitate entrée into ethnographic settings which the researcher might otherwise have difficulty accessing without changing the social dynamics that they wished to observe ( Zimmerman & Wieder, 1977 ). Since then, researchers have drawn on the methodology for other strengths, including its ability to be contemporaneous to the events and emotions recounted while capturing participant experiences over time ( Eidse & Turner, 2014 ; Taylor et al, 2019 ; Bolger et al, 2003 ). It allows researchers to explore nuances of experiences as well as changes that occur during the study period, and avoids recall bias ( Taylor et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%